2013
DOI: 10.1587/elex.10.20132007
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on quantum dot intermediate band solar cells

Abstract: Abstract:In order to surpass the thermodynamic Shockley-Queisser limit of energy conversion efficiency of single-junction solar cells, advanced concepts using multi-junction tandem structure and quantum nanostructure are presently under intense research. Recent developments and future research opportunities in high-efficiency photovoltaics technology based on quantum dot superlattice are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Light management is especially interesting for solar cells with quantum structures like multiple quantum wells (MQW), superlattices [ 57 ] or multi-stacked quantum dots [ 58 ]. Indeed, a smaller number of quantum layers is favorable for an improved carrier transport and for the reduction of dislocation density.…”
Section: New Highly Efficient Materialsmentioning
confidence: 99%
“…Light management is especially interesting for solar cells with quantum structures like multiple quantum wells (MQW), superlattices [ 57 ] or multi-stacked quantum dots [ 58 ]. Indeed, a smaller number of quantum layers is favorable for an improved carrier transport and for the reduction of dislocation density.…”
Section: New Highly Efficient Materialsmentioning
confidence: 99%
“…180 Takata et al have reported that in a well-developed cell, 181 a 50-layers stacked InAs/GaNAs QDSC with $15.7% efficiency at 1 sun has been shown to improve to efficiency of $20.3% at 100 suns and $21.2% at 1000 suns illumination. 141 Lantratov et al have reported CPV study results by using four types of different InGaAs QDSCs: with the QD media in the middle of the i-GaAs region (i-QDSC); with the same structure but using the Bragg reflector (BR-QDSC); with the QD media between i-GaAs region and n-GaAs base (base-QDSC); and in a conventional design (without QDs) keeping the i-region width of 130 nm (conv.-SC). V OC dependence on the concentration ratio was plotted in Fig.…”
Section: Concentrated Photovoltaic (Cpv) Characterizationmentioning
confidence: 99%
“…Conventional solar cells are defined here as possessing a single energy gap between the hole-and electron-conducting bands. [13][14][15][16][17] Here we report a new IB solar cell based on organic light absorbers, proposed by Ekins-Daukes and Schmidt in 2008, 12 where the intermediate band effect is achieved by energy pooling in long-lived triplet excited states, shown schematically in Fig. In IB devices, a third absorbing band or state is introduced between the valence and conduction bands, where photoexcitation into the conduction band may now occur through two means: directly by the absorption of high energy photons or by the sequential absorption of two lower-energy photons via the intermediate state.…”
Section: Introductionmentioning
confidence: 99%